Information Accessibility for Deaf Persons in Indonesia’s 2024 Presidential Debate Broadcasts - Maulana, Shakila Azzahra; Agustin, Herlina; Al-Faqih, Muhammad Zen (Jurnal Kajian Jurnalisme, 2026)
Background: The 2024 Indonesian Presidential Election debate, broadcasted by several TV stations appointed by KPU, included a sign-language interpreter (Juru Bahasa Isyarat, JBI) box on screen. Yet, Deaf advocacy organization, Gerkatin, identified recurring accessibility flaws in the first broadcast. They matter because Article 28F of the 1945 Constitution guarantees every citizen the right to seek and obtain information, including the Deaf. Purpose: This research examines how Indonesia’s broadcasting and disability legislation addressed information accessibility for Deaf voters and asks why regulatory framework derived from existing legislation produced an inaccessible broadcast. Methods: A qualitative case study design triangulated three sources: (1) legislative document analysis of Act 32/2002 on Broadcasting, Act 19/2011 ratifying the Convention on the Rights of Persons with Disabilities (CRPD), Act 8/2016 on Persons with Disabilities, and regulative document analysis of KPI’s Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS), and Dewan Pers’ Guidelines for Disability Friendly Reporting; (2) semi-structured interviews with three informants from KPI, Dewan Pers, and Bawaslu; and (3) documentary evidence of Deaf voters’ experience drawn from Gerkatin’s formal complaint and Debate Broadcast archives from YouTube. Results: Indonesia’s existing legislation acknowledges Deaf persons’ rights of information accessibility, yet P3 SPS and Guidelines for Disability-Inclusive Reporting did not translate legislation’s mandate into enforceable broadcast specifications. Interview data further indicate that regulators had engaged only with JBI associations, not with organizations of Deaf persons such as Gerkatin, in developing broadcasting practice. Conclusion: Indonesia’s existing legislation acknowledges Deaf persons’ right to information accessibility in principle but existing regulation frameworks have not translated that recognition into enforceable technical standards for information accessibility in broadcasting. Implications: Closing this gap requires measurable standards for JBI visibility and multiplicity, mandatory subtitling for high-stakes information broadcasts, and a formal collaboration with Deaf organizations.